Serologic survey of birds for West Nile flavivirus in southern Moravia (Czech Republic) - Hubálek, Z; Halouzka, J; Juricová, Z; Sikutová, S; Rudolf, I; Honza, M; Janková, J; Chytil, J; Marec, F; Sitko, J (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2008)
A serosurvey for West Nile virus (WNV) was carried out in 54 domestic birds (geese and ducks bred on fishponds) and 391 wild birds representing 28 migratory and resident species, using a plaque-reduction neutralization microtest with Vero cells and Egyptian topotype Eg-101 strain as test virus. The birds were sampled in the South-Moravian fishpond ecosystem between 2004 and 2006. Antibodies to WNV were not detected in domestic waterfowl, but 23 (5.9%) free-living birds of 10 species showed a positive response. These were the common coot (Fulica atra, 5 positive/18 examined), common kingfisher (Alcedo atthis, 1/1), reed warbler (Acrocephalus scirpaceus, 2/80), sedge warbler (A. schoenobaenus, 3/80), marsh warbler (A. palustris, 2/28), Savi's warbler (Locustella luscinioides, 3/12), reed bunting (Emberiza schoeniclus, 1/28), blackcap (Sylvia atricapilla, 2/11), penduline tit (Remiz pendulinus, 1/14), blue tit (Parus caeruleus, 1/1), and starling (Sturnus vulgaris, 2/4). The antibody titers were comparatively low (1:20-1:40), and the only high titer (1:160) was found in an adult marsh warbler. When 14 of the sera reacting with WNV were titrated in parallel with Usutu Flavivirus, 12 were interpreted as having specific antibodies to WNV, one coot had a higher titer against Usutu virus, and another one could not be attributed to either of the two viruses. In conclusion, 13 (3.3%) of 391 wild birds had specific antibodies to WNV. The results indicate that WNV activity in southern Moravia was limited during 2004-2006.
Keywords: séroepidemiologické studie; protilátky virové; Animals; západonilská horečka; nemoci ptáků; zvířata; Antibodies, Viral; Bird Diseases; Birds; ptáci; Seroepidemiologic Studies; virus západního Nilu; Czech Republic; West Nile Fever; West Nile virus; Česká republika